2019
DOI: 10.2106/jbjs.18.01419
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ligament Stabilizers of the Proximal Carpal Row in Preventing Dorsal Intercalated Segment Instability

Abstract: Background: Isolated injuries of the scapholunate interosseous ligament (SLIL) are insufficient to produce dorsal intercalated segment instability. There is no consensus about which additional ligamentous stabilizers are critical determinants of dorsal intercalated segment instability. The aim of this study was to evaluate the role of the long radiolunate (LRL), scaphotrapeziotrapezoid (STT), and dorsal intercarpal (DIC) ligaments in preventing dorsal intercalated segment instability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…Pérez et al, in a cadaveric study, evaluated the role of the scaphotrapeziotrapezoid, and dorsal intercarpal (DIC) ligaments in preventing DISI. 18 To produce that deformity, SLL injuries require the associated disruption of at least one extrinsic ligament, stabilizer of the scaphoid or lunate. Mitsuyasu et al had already highlighted the essential role of the DIC in stabilizing the scaphoid and lunate and preventing DISI deformity in cases of SLI.…”
Section: Discussionmentioning
confidence: 99%
“…Pérez et al, in a cadaveric study, evaluated the role of the scaphotrapeziotrapezoid, and dorsal intercarpal (DIC) ligaments in preventing DISI. 18 To produce that deformity, SLL injuries require the associated disruption of at least one extrinsic ligament, stabilizer of the scaphoid or lunate. Mitsuyasu et al had already highlighted the essential role of the DIC in stabilizing the scaphoid and lunate and preventing DISI deformity in cases of SLI.…”
Section: Discussionmentioning
confidence: 99%
“…DST is related to the dorsal scaphoid translation that occurs in Watson's "scaphoid shift test" 21 and to the dynamic scaphoid subluxation that occurs with wrist flexion in patients with SL dissociation. 22,23 We believe that static or dynamic dorsal scaphoid translation causes abnormal shear stress across the cartilaginous scaphoid proximal pole, with resultant painful cartilage degradation and eventual arthritic change. Various cadaveric 24,25 and clinical 26,27 studies have shown that patients with complete SLIL injuries exhibit abnormal kinematics of the carpal bones including dorsal and radial translation of the scaphoid, flexion and pronation of the scaphoid, extension and supination of the lunate, and also dorsal translation of the capitate, trapezoid, and trapezium.…”
Section: Discussionmentioning
confidence: 99%
“…The specific defects can be characterized by a variable loss of the scaphoid trapezium ligaments, the LRL, the dorsal scapholunate connection and the connection of the lunate to the DIC. Recent studies have provided additional support for the important role of the LRL and dorsal ligamentous connections (Pérez et al., 2019). A detailed explanation is beyond the summary in this article and is covered by other publications (Sandow, 2020b; Sandow and Fisher, 2020).…”
Section: Discussionmentioning
confidence: 99%